Design, construction and commissioning of the Digital Hadron Calorimeter—DHCAL. (12th July 2016) - Adams, C.; Bambaugh, A.; Bilki, B.; Butler, J.; Corriveau, F.; Cundiff, T.; Drake, G.; Francis, K.; Furst, B.; Guarino, V.; Haberichter, B.; Hazen, E.; et al.
Abstract: A novel hadron calorimeter is being developed for future lepton colliding beam detectors. The calorimeter is optimized for the application of Particle Flow Algorithms (PFAs) to the measurement of hadronic jets and features a very finely segmented readout with 1 × 1 cm 2 cells. The active media of the calorimeter are Resistive Plate Chambers (RPCs) with a digital, i.e. one-bit, readout. To first order the energy of incident particles in this calorimeter is reconstructed as being proportional to the number of pads with a signal over a given threshold. A large-scale prototype calorimeter with approximately 500, 000 readout channels has been built and underwent extensive testing in the Fermilab and CERN test beams. This paper reports on the design, construction, and commissioning of this prototype calorimeter.